Randomised controlled trial of low dose fentanyl infusion in preterm infants with hyaline membrane disease. Issue 3 (1st November 1998) - Lago, P; Benini, F; Agosto, C; Zacchello, F
Abstract : Aim— To evaluate the effects of low dose fentanyl infusion analgesia on behavioural and neuroendocrine stress response and short term outcome in premature infants ventilated for hyaline membrane disease. METHODS: Twenty seven ventilated preterm infants were randomly assigned to receive a mean fentanyl infusion of 1.1 (0.08 SE) μg/kg/h for 75 (5) hours, and 28 untreated infants were considered a control group. A behavioural sedation score was used to assess the infants' behaviour. Urinary metanephrine and the normetanephrine:creatinine molar ratio were determined at 0, 24, 48 and 72 hours. Outcome data and ventilatory indexes were recorded for each infant. RESULTS: The fentanyl group showed significantly lower behavioural stress scores and O2 desaturations than controls and lower urinary concentrations of metanephrine and normetanephrine at 24, 48, 72 hours. The two groups showed no significant difference in ventilatory variables or short term outcome. CONCLUSIONS: A short course of low dose fentanyl infusion reduces behavioural sedation scores, O2 desaturations and neuroendocrine stress response in preterm ventilated infants.